Response of Various Tomato Genotypes to Begomovirus Infection and Its Improved Diagnostic - NOOR AIDAWATI; SRI HENDRASTUTI HIDAYAT; PURNAMA HIDAYAT; RUSMILAH SUSENO; SRIANI SUJIPRIHATI (HAYATI Journal of Biosciences, 2007)
Begomovirus infection was identified from tomato growing areas in West Java (Bogor), Central Java (Boyolali), and D.I. Yogyakarta (Kaliurang). Efforts to reduce the infection among others are planting resistance varieties. This research was undertaken to evaluate 14 tomato genotypes for their response to the infection. Dot blot hybridization using nonradioactive (digoxigenin) DNA probe was employed to determine the presence of begomovirus in inoculated plants. Polymerase chain reaction-amplified product of DNA clone of tobacco leaf curl virus –Indonesia was used as a source of DNA probe. All of tomato genotypes evaluated in this study was infected separately by three strain of begomovirus (GVPSlm, GVABy, GVCBgr). Tomato genotypes Bonanza, Jelita, Safira, Permata, Presto, PSPT 8, PSPT 5B, Apel-Belgia, Karibia, Mitra, PSPT 9, Marta, and PSPT 2, showed susceptible or highly susceptible response to the three strains of begomovirus. Exception to those was shown by cv. Intan which resulted in moderate resistance when inoculated with GVCBgr although it resulted susceptible response with the other two strains. Dot-blot hybridization technique was proved to be a powerful tool to detect begomovirus infection in plants showing symptom as well as symptom-less plants. Accumulation of the virus in those plants was relatively high, except in cv. Bonanza and Apel-Belgia. Dot-blot hybridization technique using DIG-labeled DNA probe was able to detect begomovirus DNA in infected tissue up to 10-2 dilution factor. Key words: Geminivirus, hybridization, resistance, tomato